2020
DOI: 10.1177/2473974x20933566
|View full text |Cite
|
Sign up to set email alerts
|

Using Telemedicine and Infographics for Physician‐Guided Home Drain Removal

Abstract: Objective Measures to decrease hospital length of stay and outpatient visits are crucial during the coronavirus disease 2019 (COVID-19) pandemic. Physician-guided home drain removal presents a potential opportunity for mitigating viral spread and transmission. Methods A prospective case series on patients undergoing major head and neck surgery with Jackson-Pratt drain placement was conducted. Patients were shown an infographic detailing drain care and removal at preoperative assessment and prior to discharge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Outpatient postoperative management utilizing a passive drain removed at home by the patient is an additional intermediate alternative. Recent studies in head and neck oncologic surgery patients have shown promising results for self‐removable passive surgical drains 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…Outpatient postoperative management utilizing a passive drain removed at home by the patient is an additional intermediate alternative. Recent studies in head and neck oncologic surgery patients have shown promising results for self‐removable passive surgical drains 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…8 With the adoption of telemedicine during the COVID-19 pandemic, other benefits of telemedicine have been highlighted and include minimizing risk of infection for patients and providers, 9 increasing access to care for rural areas, 10 convenience and increased costeffectiveness, and shortening required length of stay in the hospital. 11 There have been policy changes to support the implementation of telemedicine within outpatient clinical workflows and specific guidelines created for telemedicine implementation. 4,12 Although many of the background studies have focused on the value of telemedicine for the patient, recent studies have begun assessing provider's experiences.…”
Section: Introductionmentioning
confidence: 99%
“… 7 They are particularly used for disseminating clinical recommendations and prevention strategies 8 9 10 11 and in telemedicine for guidance on home-based care. 12 …”
Section: Introductionmentioning
confidence: 99%